2022
DOI: 10.3390/plants11111449
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin-Based Transcriptional Reprogramming in Plants under Abiotic Stresses

Abstract: Plants’ stress response machinery is characterized by an intricate network of signaling cascades that receive and transmit environmental cues and ultimately trigger transcriptional reprogramming. The family of epigenetic regulators that are the key players in the stress-induced signaling cascade comprise of chromatin remodelers, histone modifiers, DNA modifiers and regulatory non-coding RNAs. Changes in the histone modification and DNA methylation lead to major alterations in the expression level and pattern o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 150 publications
0
8
0
Order By: Relevance
“…The plant stress response is characterized by an intricate network of signaling cascades that trigger transcriptional reprogramming 34 . To analyze the behavior of genes in A. thaliana under control conditions and under stimulus conditions, we performed differential network analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The plant stress response is characterized by an intricate network of signaling cascades that trigger transcriptional reprogramming 34 . To analyze the behavior of genes in A. thaliana under control conditions and under stimulus conditions, we performed differential network analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin accessibility and histone modifications play a significant role in plant abiotic stress responses ( Pandey et al., 2016 ; Halder et al., 2022 ; Nunez-Vazquez et al., 2022 ). Integrating chromatin regions accessibility and histone mark distribution permit to identify the location of genomic regulatory elements and understanding transcriptional regulation.…”
Section: Integrated Omics For Studying Chilling Injury Development An...mentioning
confidence: 99%
“…Several studies have demonstrated a role for histone and DNA-modifying enzymes in stress responses in the past (reviewed by Avramova, 2015;Halder et al, 2022;L€ amke & B€ aurle, 2017;Probst & Mittelsten Scheid, 2015). A series of recent studies reported the involvement of a structural protein that is associated with the nuclear envelope (NE) in plant stress responses (Choi et al, 2019;Guo et al, 2017;Jarad et al, 2019;Sakamoto et al, 2020).…”
Section: Function Of Chromatin Regulators In Biotic and Abiotic Stres...mentioning
confidence: 99%